2014
DOI: 10.1111/acer.12579
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Women Who Consume Alcohol Before and After Pregnancy Recognition in a Canadian Sample: A Prospective Cohort Study

Abstract: Common risk factors for different alcohol consumption patterns are unintended pregnancy and substance use behaviors prior to pregnancy. Other risk factors were specific to the different patterns. Targeted strategies that address the needs of alcohol or nicotine using women and that can reduce the risk of unintended pregnancy may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 43 publications
6
48
1
Order By: Relevance
“…Future research on the fetal effects of alcohol considering the gender of the conceptus may contribute to a better understanding of this specific aspect of teratogenesis. A limitation of our study is the fact that we did not investigate the use of tobacco, a habit associated with the consumption of alcohol 1,16,25,26 and known to interfere in the weight of the newborn, which may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research on the fetal effects of alcohol considering the gender of the conceptus may contribute to a better understanding of this specific aspect of teratogenesis. A limitation of our study is the fact that we did not investigate the use of tobacco, a habit associated with the consumption of alcohol 1,16,25,26 and known to interfere in the weight of the newborn, which may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition to the absence of a steady partner, other maternal risk factors commonly associated with alcohol abuse are: aged over 30 years, low education, "non-white" skin color, use of tobacco and illicit drugs, as well as socio-economic vulnerability. 16,25,26,28 A recent review showed that women who are older, have lower education, are unmarried, unemployed, with lower stature, lower body mass index, nutritional status considered suboptimal, mental health problems, who suffered sexual abuse, who had fewer prenatal consultations, who are smokers, drug users and who have partners who also consumed alcohol are at increased risk of having a child with FASD. 1 In São Paulo city, research carried out by Mesquita and Segre 10 identified 31.1% of the postpartum women as positive T-ACE.…”
Section: Variables Negative T-ace Positive T-ace P (N=758) (N=60)mentioning
confidence: 99%
“…Women who drank more than two alcoholic drinks per week or more than five alcoholic drinks per occasion (binge drinking) before they became pregnant, found it significantly more difficult to abstain entirely from drinking alcohol during pregnancy [55,60,65]. The same applied to pregnant women who had additionally smoked before or during pregnancy [55,[63][64][65][66].…”
Section: Continued Next Pagementioning
confidence: 96%
“…The same applied to pregnant women who had additionally smoked before or during pregnancy [55,[63][64][65][66]. Two of the studies found a correlation between continued maternal alcohol consumption and unplanned pregnancy [55,60]; it was not clear, however, whether nullipara or multipara found it more difficult to abstain from drinking alcohol [36]. McDonald et al [60] reported, for example, that women who had not previously given birth were more likely to binge drink during the early stages of pregnancy, i.e., before they knew they were pregnant.…”
Section: Continued Next Pagementioning
confidence: 99%
See 1 more Smart Citation